RISK FACTORS, DIAGNOSTIC CHALLENGES, AND MANAGEMENT OUTCOMES IN PEDIATRIC ASTHMA (AGES 1–12 YEARS): A PROSPECTIVE COHORT STUDY ALIGNED WITH THE GINA GUIDELINES - PUSHPARAJ NILKANTH PATIL; ZUBAIR KHAN (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: To identify risk factors for uncontrolled asthma, to evaluate diagnostic alignment with the Global Initiative for Asthma (GINA) criteria, and to assess management outcomes in children aged 1–12 years. Methods: A prospective cohort study enrolled 378 children (1–12 years) diagnosed with asthma at SVBCH Hospital, Silvassa, from January 2022 to December 2023. GINA criteria defined asthma and uncontrolled disease. Multivariate logistic regression was used to identify risk factors, and management outcomes were analyzed using Cox proportional hazards models. Results: Of 378 children (57% male, median age 6 years), 36% (n=136) had uncontrolled asthma. Significant risk factors included tobacco smoke exposure (adjusted odds ratio [aOR] 2.2, 95% confidence interval [CI]: 1.4–3.5, p<0.001), medication non-adherence (aOR 3.0, 95% CI: 1.8–4.9, p<0.001), and atopic dermatitis (aOR 1.7, 95% CI: 1.1–2.8, p=0.01). Use of controller medications reduced exacerbation risk by 42% (Hazard ratio [HR] 0.58, 95% CI: 0.42–0.79, p<0.001), and asthma action plans were associated with a 28% reduction in emergency visits (HR 0.72, 95% CI: 0.53–0.97, p=0.03). Conclusion: Strengthening GINA-compliant diagnosis, caregiver education, and environmental modifications are critical to improving outcomes in young children with asthma.